Eruption Cyst: A Case Report - Duseja, Nikita R.; Bahuguna, Rachana; Ahmed, Adnan; Veerkhare, Sumedh (Hasanuddin University, 2025)
An eruption cyst (EC) is a benign, nonodontogenic lesion. It appears as a Semi-spherical swelling in the mucosa overlying an erupting tooth. This condition occurs when the dental follicle separates from the crown, leading to the formation of a fluid-filled space. Eruption cysts usually have an epithelial lining and are encased in fibrous connective tissue.In a case involving an eleven-year-old girl, a painless, dome-shaped swelling was observed in the lower left posterior region of her jaw. This was diagnosed as an eruption cyst associated with tooth 35. An inferior alveolar nerve block was administered under local anesthesia. An access opening on tooth 75 was made and horizontal incision was given to drain the cystic fluid. Post-operative care included antibiotics and pain management. Follow-up visits showed significant healing, and subsequently pulpectomy and placement of a stainless-steel crown on tooth 75 was carried out. This case highlights the importance of conservative management for eruption cysts in pediatric patients, ensuring effective treatment while minimizing discomfort.